Alistair Grim's Odditorium - Funaro, Gregory (Disney-Hyperion, 2015)
In Victorian England Grubb, an orphan about twelve years old, escapes his life of drudgery as a chimney sweep's apprentice and finds himself in a very strange house filled with magical objects and creatures, but soon he learns that there are dark forces seeking his new master.